Preparation method of low-density and high-inertia silver-plated spherical carbon powder
By degreasing spherical toner, surface coarsing, sensitizing and silver plating treatments, low-density and high-inert silver plating spherical toners are prepared, which solves the problems of high density and poor inertia in special environments of existing conductive fillers, and achieves efficient electromagnetic shielding and long-term stable use.
Patent Information
- Application Number
- CN202510340391.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-06-27
AI Technical Summary
When used in special environments such as high heat and high salt spray, existing conductive filler materials have problems of high density and poor inertia, which is difficult to meet the needs of complex application environments.
Spherical carbon powder is used as the substrate, and low-density, high-inert silver-plated spherical carbon powder is prepared by de-oil treatment, surface roughening treatment, sensitization treatment and electroless silver plating.
The prepared silver-plated spherical toner not only has excellent conductivity and high temperature stability, but also has low density and high inertia, which can provide excellent electromagnetic shielding performance and long-term use stability in complex environments.
Smart Images

Figure CN120210791A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of conductive fillers, and particularly relates to a method for preparing silver-plated spherical carbon powder with low density and high inertness. Background Art
[0002] In recent years, with the rapid development of electromagnetic shielding materials, conductive powder materials, as the core materials of electromagnetic shielding, have important applications in the fields of conductive rubber, conductive glue and other composite electromagnetic shielding materials.
[0003] Currently, common electromagnetic shielding conductive fillers include silver powder, silver-plated copper powder, silver-plated aluminum powder, silver-plated glass microspheres and nickel-plated graphite, etc. Among them, silver powder is expensive and has a very high density, and is currently only used in conductive adhesives requiring high conductivity; silver-plated copper powder has a wide range of applications in multiple fields due to the different shapes of the substrates, but it has disadvantages such as high density and easy oxidation of copper at high temperatures; although silver-plated aluminum powder has high conductivity and a relatively moderate density, due to the active nature of the substrate metal, it is difficult to be directly applied in special environments; the density of silver-plated glass microspheres is relatively small, however, the conductivity of the substrate is poor, and there is a risk of breakage and damage of the glass microspheres in a high-frequency vibration environment; nickel-plated graphite has stable performance, but its conductivity is average and its density is also large. The above common conductive fillers generally have the characteristics of high density and poor inertness, and are difficult to be used in special environments such as high heat and high salt spray.
[0004] In view of this, this invention is specifically proposed. Summary of the Invention
[0005] The purpose of the present invention is to overcome the above-mentioned disadvantages of the prior art, and provide a method for preparing silver-plated spherical carbon powder with low density and high inertness. Spherical carbon powder is used as the substrate, and after a special surface pretreatment process, chemical silver plating is carried out to endow the carbon powder with good conductivity, and silver-plated spherical carbon powder is prepared. The silver-plated spherical carbon powder not only exhibits excellent conductivity, but also has the low density, high inertness, excellent mechanical properties and extremely high high-temperature stability of spherical carbon powder. As a conductive filling material, the electromagnetic shielding composite material prepared from silver-plated spherical carbon powder can adapt to complex application environments, can provide excellent conductivity and electromagnetic shielding performance, the lower density can reduce the specific gravity of the material, and it shows good inertness in high-temperature, high-heat, high-salt spray and complex chemical environments, improving the service life and stability of the material.
[0006] The purpose of the present invention is solved by the following technical solutions:
[0007] The present invention provides a method for preparing silver-plated spherical carbon powder with low density and high inertness, comprising the following steps:
[0008] Step 1. Pretreatment: First, add spherical carbon powder into the pre-prepared degreasing solution for degreasing treatment, then wash and filter with deionized water. Next, add the filtered spherical carbon powder into the pre-prepared etching solution for surface roughening treatment. After drying, the pretreated spherical carbon powder is obtained.
[0009] Step 2. Sensitization treatment: First, add the spherical carbon powder obtained by pretreatment in Step 1 into the pre-prepared sensitizing solution for sensitization reaction, and then dry to obtain the spherical carbon powder after sensitization reaction.
[0010] Step 3. Electroless silver plating: First, add the spherical powder obtained by sensitization reaction in Step 2 into the pre-prepared oxidation solution for activation treatment, then add the prepared reducing solution into the oxidation solution, heat in a water bath at 30°C - 60°C, react for 2h - 4h, and then obtain silver-plated spherical carbon powder after washing, filtering and drying.
[0011] Furthermore, both the degreasing treatment and the surface roughening treatment in Step 1 are water bath heating and mechanical stirring treatments.
[0012] Among them, the water bath temperature is 30°C - 50°C, the stirring rate is 500r / min - 1000r / min, and the reaction time is 10min - 30min.
[0013] Furthermore, the degreasing solution in Step 1 is prepared by mixing a degreasing agent and deionized water according to a mass ratio of 0.2 - 1:10.
[0014] Among them, the degreasing agent is any one or more of ethanol, sodium hydroxide and sodium carbonate.
[0015] When performing degreasing treatment, the mass ratio of the degreasing solution to the spherical carbon powder is 50 - 200:1.
[0016] Furthermore, the etching solution in Step 1 is prepared by mixing an etching agent and deionized water according to a mass ratio of 1 - 2:20.
[0017] Among them, the etching agent is any one or more of nitric acid, hydrochloric acid and sulfuric acid.
[0018] When performing surface roughening treatment, the mass ratio of the etching solution to the spherical carbon powder is 50 - 100:1.
[0019] Furthermore, the sensitization treatment in Step 2 is a water bath heating and mechanical stirring treatment.
[0020] Among them, the water bath temperature is 20°C - 40°C, the stirring rate is 500r / min - 1000r / min, and the stirring time is 1h - 4h.
[0021] Further, the preparation steps of the sensitizing solution in step two are as follows: Add the sensitizer to concentrated hydrochloric acid and dissolve it, then dilute it with deionized water to a preset concentration to obtain the sensitizing solution;
[0022] Among them, the sensitizer is stannous chloride or palladium chloride, the concentration of the concentrated hydrochloric acid is 10 g / L - 30 g / L, the mass ratio of the sensitizer to the concentrated hydrochloric acid is 1 - 3:6, and the preset concentration is 10 g / L - 30 g / L;
[0023] When performing the sensitization treatment, the mass ratio of the spherical carbon powder to the sensitizing solution is 1 - 3:3.
[0024] Further, the activation treatment in step three is a water bath heating and mechanical stirring treatment,
[0025] Among them, the water bath temperature is 30°C - 40°C, the stirring rate is 500 r / min - 1000 r / min, and the stirring time is 0.5 h - 1 h.
[0026] Further, the preparation steps of the oxidation solution in step three are as follows: Dissolve the silver salt in deionized water. When the silver salt is completely dissolved, start to dropwise add concentrated ammonia water while stirring. At this time, the solution becomes turbid. Continue to dropwise add until the solution just becomes clear, then stop dropping to obtain the oxidation solution;
[0027] Among them, the concentrated ammonia water is 25% - 28% analytical pure;
[0028] When performing the activation treatment, the mass ratio of the silver salt to the spherical carbon powder is 4 - 6:5, and the concentration of the silver salt dissolved in deionized water is 10 g / L - 15 g / L.
[0029] Further, the reducing solution is prepared from a reducing agent, a surfactant, a stabilizer, and deionized water according to a mass ratio of 8 - 12:1 - 3:40 - 60:1000, and is completely dissolved by mechanical stirring. Among them, the stirring rate is 500 r / min - 1000 r / min, and the stirring time is 5 min - 10 min;
[0030] Add the prepared reducing solution to the oxidation solution, and the volume ratio of the reducing solution to the oxidation solution is 1:1;
[0031] The reducing agent is any one or more of formaldehyde, glucose, tartaric acid, and sodium potassium tartrate,
[0032] Among them, the concentration of formaldehyde is 3 ml / L - 10 ml / L, the concentration of glucose is 8 g / L - 10 g / L, the concentration of tartaric acid is 1 g / L - 1.25 g / L; the concentration of sodium potassium tartrate is 20 g / L - 40 g / L;
[0033] The surfactant is any one of polyethylene glycol, polyvinylpyrrolidone, OP-10, sodium dodecylbenzenesulfonate, and gelatin,
[0034] wherein the concentration of the polyethylene glycol is 0.1 g / L - 1 g / L, the concentration of the polyvinylpyrrolidone is 1.5 g / L - 3 g / L; the concentration of the OP-10 is 3 ml / L - 5 ml / L, the concentration of the sodium dodecylbenzenesulfonate is 0.01 g / L - 0.1 g / L, and the gelatin is of analytical purity with a concentration of 0.1 g / L - 1 g / L;
[0035] The stabilizer is any one of ethanol, methanol, and ethylene glycol,
[0036] wherein the concentration of the ethanol is 40 g / L - 60 g / L, the concentration of the methanol is 50 g / L - 100 g / L, and the concentration of the ethylene glycol is 50 g / L - 100 g / L.
[0037] Furthermore, the temperature of the drying treatment in steps 1 to 3 is 80°C - 120°C, and the drying time is 4 h - 8 h.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. The silver-plated spherical carbon powder prepared by the preparation method of the present invention not only exhibits excellent electrical conductivity, but also has the low density, high inertness, excellent mechanical properties, and extremely high high-temperature stability of the spherical carbon powder;
[0040] 2. The silver-plated spherical carbon powder prepared by the present invention, as a conductive filler material, the electromagnetic shielding composite material prepared therefrom can adapt to complex application environments, can provide excellent electrical conductivity and electromagnetic shielding performance, the lower density can reduce the specific gravity of the material, and it shows good inertness in high-temperature, high-salt spray, and complex chemical environments, improving the service life and stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The accompanying drawings herein are incorporated into the specification and form a part of the specification, and are used together with the specification to explain the principles of the present invention.
[0042] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, for those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0043] Figure 1 is a flow chart of the preparation method of the low-density and high-inertness silver-plated spherical carbon powder of the present invention;
[0044] Figure 2 SEM morphology diagram of the silver-plated spherical carbon powder prepared in Example 1 of the present invention at a magnification of 10,000 times;
[0045] Figure 3 SEM morphology diagram of the silver-plated spherical carbon powder prepared in Example 1 of the present invention at a magnification of 5,000 times. Detailed implementation manners
[0046] Here, the exemplary embodiments will be described in detail, and the examples are shown in the drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementation manners described in the following exemplary embodiments do not represent all implementation manners consistent with the present invention. On the contrary, they are only examples consistent with some aspects of the present invention detailed in the appended claims.
[0047] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below in conjunction with the drawings and embodiments.
[0048] Refer to the attached Figure 1 As shown, the present invention provides a method for preparing a low-density and highly inert silver-plated spherical carbon powder, including the following steps:
[0049] Step 1. Pretreatment.
[0050] Weigh the degreasing agent and deionized water in proportion to prepare the degreasing solution, and weigh the etching agent and deionized water in proportion to prepare the etching solution; add the spherical carbon powder to the degreasing solution in proportion for degreasing treatment. After the degreasing treatment, wash the residue with deionized water and filter to obtain the spherical carbon powder; transfer the obtained spherical carbon powder to the etching solution for surface roughening treatment to increase the specific surface area of the spherical carbon powder, thereby improving the surface activity of the spherical carbon powder; after the surface roughening treatment, dry the spherical carbon powder after surface roughening treatment to obtain the pretreated spherical carbon powder.
[0051] Both the degreasing treatment and the surface roughening treatment are water bath heating and mechanical stirring treatments, where the water bath temperature is 30°C - 50°C, the stirring rate is 500 r / min - 1000 r / min, and the reaction time is 10 min - 30 min.
[0052] The degreasing solution is prepared from the degreasing agent and deionized water according to a mass ratio of 0.2 - 1:10. Preferably, the mass ratio of the degreasing agent to deionized water is 1:10; among them, the degreasing agent is any one or more of ethanol, sodium hydroxide, and sodium carbonate, and preferably the degreasing agent is ethanol.
[0053] When performing degreasing treatment, the mass ratio of the degreasing solution to the spherical carbon powder is 50 - 200:1. Preferably, the mass ratio of the degreasing solution to the spherical carbon powder is 100:1.
[0054] The etching solution is prepared by mixing an etchant and deionized water in a mass ratio of 1 - 2:20. Preferably, the mass ratio of the etchant to deionized water is 1:10. Among them, the etchant is any one or more of nitric acid, hydrochloric acid, and sulfuric acid. Preferably, the etchant is sulfuric acid.
[0055] When performing surface roughening treatment, the mass ratio of the etching solution to the spherical carbon powder is 50 - 100:1. Preferably, the mass ratio of the etching solution to the spherical carbon powder is 100:1.
[0056] The temperature for drying treatment is 80°C - 120°C, and the drying time is 4h - 8h. Preferably, the drying temperature is 80°C, and the drying time is 6h.
[0057] Step 2: Sensitization treatment.
[0058] Weigh the sensitizer in proportion, mix the weighed sensitizer with concentrated hydrochloric acid. After the weighed sensitizer is completely dissolved, dilute it with deionized water to a preset concentration to obtain a sensitizing solution. Weigh the pretreated spherical carbon powder in proportion, place the weighed spherical carbon powder in the sensitizing solution for sensitization reaction, and perform drying treatment after the reaction ends to obtain the spherical carbon powder after sensitization reaction.
[0059] The sensitization treatment is a water bath heating and mechanical stirring treatment. Among them, the water bath temperature is 20°C - 40°C, the stirring rate is 500r / min - 1000r / min, and the stirring time is 1h - 4h.
[0060] The sensitizer is stannous chloride or palladium chloride. The concentration of the concentrated hydrochloric acid is 10g / L - 30g / L. The mass ratio of the sensitizer to the concentrated hydrochloric acid is 1 - 3:6. Preferably, the mass ratio of the sensitizer to the concentrated hydrochloric acid is 2:6. The preset concentration is 10g / L - 30g / L. Preferably, the preset concentration is 20g / L.
[0061] When performing sensitization treatment, the mass ratio of the spherical carbon powder to the sensitizing solution is 1 - 3:3. Preferably, the mass ratio of the spherical carbon powder to the sensitizing solution is 2:3.
[0062] The temperature for drying treatment is 80°C - 120°C, and the drying time is 4h - 8h. Preferably, the drying temperature is 80°C, and the drying time is 6h.
[0063] Step 3: Electroless silver plating.
[0064] Weigh silver salt and deionized water proportionally to prepare the oxidation liquid, and add the spherical carbon powder after sensitization reaction to the oxidation liquid according to the proportion for activation treatment; Weigh the reducing agent, surfactant and stabilizer proportionally, dissolve the weighed reducing agent, surfactant and stabilizer in deionized water, and completely dissolve them by mechanical stirring at a stirring rate of 500 r / min - 1000 r / min for a stirring time of 5 min - 10 min to obtain the reducing liquid after uniform stirring; Pour the reducing liquid into the oxidation liquid, heat it in a water bath to 30°C - 60°C for reaction, after reacting for 2 h - 4 h, wash the residues with deionized water and filter the powder, and obtain silver-plated spherical carbon powder after drying treatment.
[0065] The activation treatment is water bath heating and mechanical stirring treatment. Among them, the water bath temperature is 30°C - 40°C, the stirring rate is 500 r / min - 1000 r / min, and the stirring time is 0.5 h - 1 h.
[0066] The silver salt is silver nitrate, and the concentrated ammonia water is analytical pure with a concentration of 25% - 28%. The preparation steps of the oxidation liquid are as follows: Dissolve the silver salt in deionized water, start to dropwise add concentrated ammonia water when the silver salt is completely dissolved, stir while adding. At this time, the solution becomes turbid. Continue to add dropwise until the solution just becomes clear and then stop adding to obtain the oxidation liquid.
[0067] When performing the activation treatment, the mass ratio of the silver salt to the spherical carbon powder is 4 - 6:5, and the concentration of the silver salt dissolved in deionized water is 10 g / L - 15 g / L.
[0068] The reducing liquid is prepared from a reducing agent, a surfactant, a stabilizer and deionized water according to a mass ratio of 9 - 12:1 - 3:40 - 60:1000, and is completely dissolved by mechanical stirring. Among them, the stirring rate is 500 r / min - 1000 r / min, and the stirring time is 5 min - 10 min.
[0069] The volume ratio of the reducing liquid to the oxidation liquid is 1:1.
[0070] The reducing agent is any one or more of formaldehyde, glucose, tartaric acid and sodium potassium tartrate. Among them, the concentration of formaldehyde is 3 ml / L - 10 ml / L, the concentration of glucose is 8 g / L - 10 g / L, the concentration of tartaric acid is 1 g / L - 1.25 g / L; the concentration of sodium potassium tartrate is 20 g / L - 40 g / L.
[0071] The surfactant is any one of polyethylene glycol, polyvinylpyrrolidone, OP-10, sodium dodecylbenzenesulfonate, and gelatin. Among them, the concentration of polyethylene glycol is 0.1 g / L - 1 g / L, the concentration of polyvinylpyrrolidone is 1.5 g / L - 3 g / L; the concentration of OP-10 is 3 ml / L - 5 ml / L, the concentration of sodium dodecylbenzenesulfonate is 0.01 g / L - 0.1 g / L, and the gelatin is of analytical purity with a concentration of 0.1 g / L - 1 g / L.
[0072] The stabilizer is any one of ethanol, methanol, and ethylene glycol. Among them, the concentration of ethanol is 40 g / L - 60 g / L, the concentration of methanol is 50 g / L - 100 g / L, and the concentration of ethylene glycol is 50 g / L - 100 g / L.
[0073] The temperature of the drying treatment is 80°C - 120°C, and the drying time is 4 h - 8 h; preferably, the drying temperature is 80°C and the drying time is 6 h.
[0074] In order to verify the beneficial effects brought by the preparation method of the present invention, it is further illustrated through the following examples. It should be noted that all parts mentioned in the following examples are parts by weight.
[0075] Example 1
[0076] A preparation method of low-density and highly inert silver-plated spherical carbon powder provided in this example includes the following steps:
[0077] Step 1: Pretreatment.
[0078] Take 10 parts of sodium hydroxide and dissolve it in 100 parts of deionized water to prepare a degreasing solution, take 10 parts of sulfuric acid and dissolve it in 100 parts of deionized water to prepare an etching solution. Add 1 part of spherical carbon powder to the degreasing solution, and carry out degreasing treatment at a water bath temperature of 40°C and a stirring rate of 600 r / min. After stirring for 20 min, wash the residue on the surface of the spherical carbon powder with deionized water, and filter out the spherical carbon powder; then transfer the spherical carbon powder to the etching solution, and carry out surface roughening treatment at a water bath temperature of 40°C and a stirring rate of 600 r / min. The reaction time is 20 min to increase the specific surface area of the spherical carbon powder, thereby improving the surface activity of the spherical carbon powder; after the surface roughening treatment is completed, dry the surface-roughened spherical carbon powder at 80°C for 6 h to obtain the pretreated spherical carbon powder.
[0079] Step 2: Sensitization treatment.
[0080] Take 2 parts of stannous chloride and dissolve it in 6 parts of concentrated hydrochloric acid. After complete dissolution, dilute the concentration of stannous chloride to 20 g / L with deionized water to prepare a sensitizing solution. Then, take 2 parts of pretreated spherical carbon powder and put it into the sensitizing solution. The mass ratio of spherical carbon powder to the sensitizing solution is 1:3. Carry out the sensitization reaction at a water bath temperature of 40 °C and a stirring rate of 600 r / min for 2 h. After the reaction, dry it at 80 °C for 6 h to obtain the spherical carbon powder after the sensitization reaction.
[0081] Step 3: Electroless silver plating.
[0082] Take 4 parts of silver nitrate and dissolve it in 500 parts of deionized water to prepare an oxidation solution. Take 5 parts of the sensitized spherical carbon powder and add it to the oxidation solution. Carry out the activation treatment at a water bath temperature of 30 °C and a stirring rate of 1000 r / min for 0.5 h. After the activation treatment, take 4 parts of glucose, 0.5 part of tartaric acid, 0.75 part of polyvinylpyrrolidone and 20 parts of ethanol and dissolve them in 1000 parts of deionized water to prepare a reduction solution. Stir at a stirring rate of 600 r / min for 6 min. After mechanical stirring evenly, pour the reduction solution into the oxidation solution, heat it in a water bath to 40 °C for reaction. After 3 h of reaction, wash the residue on the surface of the powder with deionized water and filter the powder. Finally, dry it at 80 °C for 6 h to obtain the silver-plated spherical carbon powder. As Figures 2-3 This is the SEM morphology diagram of the silver-plated spherical carbon powder prepared in this example.
[0083] Example 2
[0084] Step 1: Pretreatment.
[0085] Take 1 part of ethanol and dissolve it in 50 parts of deionized water to prepare a degreasing solution. Take 5 parts of hydrochloric acid and dissolve it in 100 parts of deionized water to prepare an etching solution. Add 1 part of spherical carbon powder to the degreasing solution. Carry out the degreasing treatment at a water bath temperature of 30 °C and a stirring rate of 500 r / min for 30 min. Then wash the residue on the surface of the spherical carbon powder with deionized water and filter out the spherical carbon powder. Then transfer the spherical carbon powder to the etching solution and carry out the surface roughening treatment at a water bath temperature of 30 °C and a stirring rate of 500 r / min for 30 min to increase the specific surface area of the spherical carbon powder and thus improve the surface activity of the spherical carbon powder. After the surface roughening treatment, dry the surface-roughened spherical carbon powder at 100 °C for 5 h to obtain the pretreated spherical carbon powder.
[0086] Step 2: Sensitization treatment.
[0087] Dissolve 3 parts of stannous chloride in 6 parts of concentrated hydrochloric acid. After complete dissolution, dilute the concentration of stannous chloride to 30 g / L with deionized water to prepare a sensitizing solution. Then, take 2 parts of pretreated spherical carbon powder and put it into the sensitizing solution. The mass ratio of the spherical carbon powder to the sensitizing solution is 2:3. Carry out the sensitization reaction at a water bath temperature of 30 °C and a stirring rate of 800 r / min. The stirring time is 4 h. After the reaction is completed, dry it at 100 °C for 5 h to obtain the spherical carbon powder after the sensitization reaction.
[0088] Step 3: Electroless silver plating.
[0089] Dissolve 5 parts of silver nitrate in 500 parts of deionized water to prepare an oxidation solution. Take 5 parts of sensitized spherical carbon powder and add it to the oxidation solution. Carry out the activation treatment at a water bath temperature of 35 °C and a stirring rate of 750 r / min. The stirring time is 0.7 h; after the activation treatment is completed, dissolve 5 parts of formaldehyde, 5 parts of tartaric acid, 2 parts of polyethylene glycol and 50 parts of methanol in 1000 parts of deionized water to prepare a reduction solution. Stir at a stirring rate of 500 r / min for 10 min. After mechanical stirring is uniform, pour the reduction solution into the oxidation solution. Heat it in a water bath to 30 °C for reaction. After 4 h of reaction, wash the residual substances on the surface of the powder with deionized water and filter the powder. Finally, dry it at 100 °C for 5 h to obtain silver-plated spherical carbon powder.
[0090] Example 3
[0091] Step 1: Pretreatment.
[0092] Dissolve 2 parts of sodium carbonate in 100 parts of deionized water to prepare a degreasing solution. Dissolve 8 parts of nitric acid in 100 parts of deionized water to prepare an etching solution. Add 1 part of spherical carbon powder to the degreasing solution. Carry out the degreasing treatment at a water bath temperature of 50 °C and a stirring rate of 1000 r / min. After 10 min of stirring, wash the residual substances on the surface of the spherical carbon powder with deionized water and filter out the spherical carbon powder; then transfer the spherical carbon powder to the etching solution. Carry out the surface roughening treatment at a water bath temperature of 50 °C and a stirring rate of 1000 r / min. The reaction time is 10 min to increase the specific surface area of the spherical carbon powder and thus improve the surface activity of the spherical carbon powder; after the surface roughening treatment is completed, dry the surface-roughened spherical carbon powder at 120 °C for 4 h to obtain the pretreated spherical carbon powder.
[0093] Step 2: Sensitization treatment.
[0094] Take 2 parts of palladium chloride and dissolve it in 6 parts of concentrated hydrochloric acid. After complete dissolution, dilute the concentration of palladium chloride to 10 g / L with deionized water to prepare a sensitizing solution. Then, take 2 parts of pretreated spherical carbon powder and put it into the sensitizing solution. The mass ratio of the spherical carbon powder to the sensitizing solution is 1:1. Carry out the sensitization reaction at a water bath temperature of 20 °C and a stirring rate of 1000 r / min for 1 h. After the reaction, dry it at 80 °C for 6 h to obtain the spherical carbon powder after the sensitization reaction.
[0095] Step 3: Electroless silver plating.
[0096] Take 6 parts of silver nitrate and dissolve it in 500 parts of deionized water to prepare an oxidation solution. Take 5 parts of the sensitized spherical carbon powder and add it to the oxidation solution. Carry out the activation treatment at a water bath temperature of 40 °C and a stirring rate of 500 r / min for 10.5 h. After the activation treatment, take 12 parts of potassium sodium tartrate, 3 parts of sodium dodecylbenzenesulfonate, and 60 parts of ethylene glycol and dissolve them in 1000 parts of deionized water to prepare a reducing solution. Stir it at a stirring rate of 1000 r / min for 5 min. After mechanical stirring evenly, pour the reducing solution into the oxidation solution, heat it to 60 °C in a water bath for reaction. After 2 h of reaction, wash the residue on the surface of the powder with deionized water and filter the powder. Finally, dry it at 120 °C for 4 h to obtain the silver-plated spherical carbon powder.
[0097] In order to further verify the beneficial effects of the silver-plated spherical carbon powder obtained in the above embodiments of the present invention, the following performance tests are carried out.
[0098] The test data of the silver-plated spherical carbon powder prepared in Examples 1-3 are shown in Table 1.
[0099] Table 1 Test data table of silver-plated spherical carbon powder
[0100]
[0101] As can be seen from Table 1, the silver-plated spherical carbon powder prepared by the preparation method of the present invention is used as a conductive filler, which has the characteristics of low density and high inertness, and the resistance of the conductive filler changes little when used in special environments such as high heat and high salt spray.
[0102] The above are only specific embodiments of the present invention, enabling those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be obvious to those skilled in the art. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.
[0103] It should be understood that the present invention is not limited to the above-described content and can be modified and changed without departing from its scope. The scope of the present invention is only limited by the appended claims.
Claims
1. A method for preparing low-density, high-inertness silver-plated spherical carbon powder, characterized in that: The steps include: Step 1, pretreatment: firstly, the spherical carbon powder is added into a pre-prepared degreasing liquid for degreasing treatment, then washed with deionized water and filtered, then the filtered spherical carbon powder is added into a pre-prepared etching liquid for surface roughening treatment, and the pre-treated spherical carbon powder is obtained after drying; Step 2: Sensitization treatment: firstly, the spherical carbon powder obtained by the pretreatment in step 1 is added into the pre-prepared sensitization solution for sensitization reaction, and then dried to obtain the spherical carbon powder after sensitization reaction; Step 3, chemical silver plating: first add the spherical powder obtained by the sensitization reaction in step 2 into the pre-prepared oxidizing solution for activation treatment, then add the prepared reducing solution into the oxidizing solution, heat it in a water bath to 30°C-60°C, react for 2h-4h, and then obtain the silver-plated spherical carbon powder after washing, filtering and drying.
2. The method for preparing low-density, high-inertness silver-plated spherical carbon powder according to claim 1, characterized in that: The degreasing treatment and surface roughening treatment in step 1 are both water bath heating and mechanical stirring treatment. The water bath temperature is 30°C-50°C, the stirring rate is 500r / min-1000r / min, and the reaction time is 10min-30min.
3. The method for preparing low-density, high-inertness silver-plated spherical carbon powder according to claim 1, characterized in that: The degreasing liquid in step 1 is prepared by mixing a degreasing agent and deionized water in a mass ratio of 0.2-1:10; Wherein, the degreasing agent is any one or more of ethanol, sodium hydroxide and sodium carbonate; When performing degreasing treatment, the mass ratio of the degreasing liquid to the spherical carbon powder is 50-200:
1.
4. The method for preparing low-density, high-inertness silver-plated spherical carbon powder according to claim 1, characterized in that: The etching solution in step 1 is prepared by mixing the etching agent and deionized water in a mass ratio of 1-2:20; Wherein, the corrosive agent is any one or more of nitric acid, hydrochloric acid and sulfuric acid; When performing the surface roughening treatment, the mass ratio of the etching liquid to the spherical carbon powder is 50-100:
1.
5. The method for preparing low-density, high-inertness silver-plated spherical carbon powder according to claim 1, characterized in that: The sensitization treatment in step 2 is a water bath heating and mechanical stirring treatment. The water bath temperature is 20°C-40°C, the stirring rate is 500r / min-1000r / min, and the stirring time is 1h-4h.
6. The method for preparing low-density, high-inertness silver-plated spherical carbon powder according to claim 1, characterized in that: The preparation steps of the sensitizing solution in step 2 are: adding the sensitizer into concentrated hydrochloric acid to dissolve it, and then diluting it with deionized water to a preset concentration to obtain the sensitizing solution; Wherein, the sensitizer is stannous chloride or palladium chloride, the concentration of the concentrated hydrochloric acid is 10g / L-30g / L, the mass ratio of the sensitizer to the concentrated hydrochloric acid is 1-3:6, and the preset concentration is 10g / L-30g / L; During the sensitization treatment, the mass ratio of the spherical carbon powder to the sensitizing solution is 1-3:
3.
7. The method for preparing low-density, high-inertness silver-plated spherical carbon powder according to claim 1, characterized in that: The activation treatment in step 3 is a water bath heating and mechanical stirring treatment. The water bath temperature is 30°C-40°C, the stirring rate is 500r / min-1000r / min, and the stirring time is 0.5h-1h.
8. The method for preparing low-density, high-inertness silver-plated spherical carbon powder according to claim 1, characterized in that: The preparation steps of the oxidation solution in step 3 are as follows: dissolving the silver salt in deionized water, and starting to drop concentrated ammonia water when the silver salt is completely dissolved, stirring while dropping, at this time, the solution becomes turbid, continue to drop, and stop dropping when the solution is just clear, to obtain the oxidation solution; Wherein, the concentrated ammonia water is 25%-28% analytical grade; During the activation treatment, the mass ratio of the silver salt to the spherical carbon powder is 4-6:5, and the concentration of the silver salt dissolved in deionized water is 10g / L-15g / L.
9. The method for preparing low-density, high-inertness silver-plated spherical carbon powder according to claim 1, characterized in that: The reducing liquid is prepared from a reducing agent, a surfactant, a stabilizer and deionized water in a mass ratio of 8-12:1-3:40-60:1000, and is completely dissolved by mechanical stirring, wherein the stirring rate is 500r / min-1000r / min, and the stirring time is 5min-10min; Add the prepared reducing solution into the oxidizing solution, wherein the volume ratio of the reducing solution to the oxidizing solution is 1:1; The reducing agent is any one or more of formaldehyde, glucose, tartaric acid and potassium sodium tartrate, wherein the concentration of the formaldehyde is 3ml / L-10ml / L, the concentration of the glucose is 8g / L-10g / L, the concentration of the tartaric acid is 1g / L-1.25g / L; the concentration of the potassium sodium tartrate is 20g / L-40g / L; The surfactant is any one of polyethylene glycol, polyvinyl pyrrolidone, OP-10, sodium dodecylbenzene sulfonate and gelatin. Wherein, the concentration of polyethylene glycol is 0.1g / L-1g / L, the concentration of polyvinyl pyrrolidone is 1.5g / L-3g / L; the concentration of OP-10 is 3ml / L-5ml / L, the concentration of sodium dodecylbenzene sulfonate is 0.01g / L-0.1g / L, and the gelatin is analytically pure with a concentration of 0.1g / L-1g / L; The stabilizer is any one of ethanol, methanol and ethylene glycol, Wherein, the concentration of the ethanol is 40g / L-60g / L, the concentration of the methanol is 50g / L-100g / L, and the concentration of the ethylene glycol is 50g / L-100g / L.
10. The method for preparing low-density, high-inertness silver-plated spherical carbon powder according to claim 1, characterized in that: The temperature of the drying treatment in step 1 to step 3 is 80° C.-120° C., and the drying time is 4 h-8 h.